Conceptualising the agency of highly marginalised women: Intimate partner violence in extreme settings. Issue 1 (7th February 2016) - Campbell, Catherine; Mannell, Jenevieve
Abstract : How is the agency of women best conceptualised in highly coercive settings? We explore this in the context of international efforts to reduce intimate partner violence (IPV) against women in heterosexual relationships. Articles critique the tendency to think of women's agency and programme endpoints in terms of individual actions, such as reporting violent men or leaving violent relationships, whilst neglecting the interlocking social, economic and cultural contexts that make such actions unlikely or impossible. Three themes cut across the articles. (1) Unhelpful understandings of gender and power implicit in commonly used 'men-women' and 'victim-agent' binaries obscure multi-faceted and hidden forms of women's agency, and the complexity of agency-violence intersections. (2) This neglect of complexity results in a poor fit between policy and interventions to reduce IPV, and women's lives. (3) Such neglect also obscures the multiplicities of women's agency, including the competing challenges they juggle alongside IPV, differing levels of response, and the temporality of agency. We outline a notion of 'distributed agency' as a multi-level, incremental and non-linear process distributed across time, space and social networks, and across a continuum of action ranging from survival to resistance. This understanding of agency implies a different approach to those currently underpinning policies and interventions.